KEDUDUKAN HARTA DAN PERMASALAHANNYA - Irdaningsih, Irdaningsih; Nasution, Fahrurozi; Ikhwan, Muhammad (STAI Darul Quran Payakumbuh, 2024)
Abstrack The author interprets and explains the position of property and the function of property itself in Islam. The results of this discussion are: 1. The position of assets 2. The functions of assets in accordance with sharia' include: Perfection of mahdhah worship, Maintaining and increasing faith and devotion to Allah SWT, Continuing the relay of life, Harmonizing life in this world and the hereafter, Provisions for finding and develop knowledge, Harmony in state and society, To rotate the roles of life, To foster friendship.,3. Division of assets as a result of law, 4. Gift of property. Property ownership is based on the following principles: Trust, Infradhiyah, ijtima'iyah and benefits. Maintaining assets is the last in the five elements of benefit, but according to the author, assets are the main milestone in maintaining the five maqashid of sharia (shariah goals). By having sufficient wealth, all five benefits (religion, soul, intellect, offspring and wealth) will be fulfilled. This research uses qualitative research with a literature review approach. Abstrak Penulis menginterprestasikan dan menjelaskan tentang kedudukan harta dan fungsi harta sendiri dalam Islam. Hasil dari pembahasan ini adalah: 1. Kedudukan harta 2.Fungsi harta yang sesuai dengan syara’ antara lain untuk: Kesempurnaan ibadah mahdhah, Memelihara dan meningkatkan keimanan dan ketaqwaan kepada Allah SWT, Meneruskan estafet kehidupan, Menyelaraskan antara kehidupan dunia dan akhirat, Bekal mencari dan mengembangkan ilmu, Keharmonisan hidup bernegara dan bermasyarakat, Untuk memutarkan peranan-peranan kehidupan, Untuk menumbuhkan silaturrahim.,3. Pembagian harta akibat hukum,4. Pemberian harta. Kepemilikan harta di dasarkan pada asas sebagai berikut: Amanah, Infradhiyah, ijtima’iyah dan manfaat. Memelihara harta merupakan urutan terakhir dalam lima unsur kemaslahatan, namun menurut penulis harta merupakan tonggak utama dalam memelihara kelima maqashid syariah (tujuan syariah). Dengan memiliki harta yang cukup akan terpenuhi semua lima maslahat (agama, jiwa,akal, keturunan dan harta). Penelitan ini menggunakan penelitian kualitatif dengan pendekatan literatur review.